The Roles of Matrix Metalloproteinases and Their Inhibitors in Human Diseases - Cabral-Pacheco, Griselda A; Garza-Veloz, Idalia; Castruita-De la Rosa, Claudia; Ramirez-Acuña, Jesús M; Perez-Romero, Braulio A; Guerrero-Rodriguez, Jesús F; Martinez-Avila, Nadia; Martinez-Fierro, Margarita L (International journal of molecular sciences, 2020)
Matrix metalloproteinases (MMPs) are a family of zinc-dependent extracellular matrix (ECM) remodeling endopeptidases that have the capacity to degrade almost every component of the ECM. The degradation of the ECM is of great importance, since it is related to embryonic development and angiogenesis. It is also involved in cell repair and the remodeling of tissues. When the expression of MMPs is altered, it can generate the abnormal degradation of the ECM. This is the initial cause of the development of chronic degenerative diseases and vascular complications generated by diabetes. In addition, this process has an association with neurodegeneration and cancer progression. Within the ECM, the tissue inhibitors of MMPs (TIMPs) inhibit the proteolytic activity of MMPs. TIMPs are important regulators of ECM turnover, tissue remodeling, and cellular behavior. Therefore, TIMPs (similar to MMPs) modulate angiogenesis, cell proliferation, and apoptosis. An interruption in the balance between MMPs and TIMPs has been implicated in the pathophysiology and progression of several diseases. This review focuses on the participation of both MMPs (e.g., MMP-2 and MMP-9) and TIMPs (e.g., TIMP-1 and TIMP-3) in physiological processes and on how their abnormal regulation is associated with human diseases. The inclusion of current strategies and mechanisms of MMP inhibition in the development of new therapies targeting MMPs was also considered.